Superconductivity in a misfit compound (PbSe)1.12(TaSe2). (2nd November 2018) - Yang, Xiaohui; Wang, Mengmeng; Li, Yupeng; Bai, Hua; Ma, Jiang; Sun, Xikang; Tao, Qian; Dong, Cheng; Xu, Zhu-An
Abstract: We report the discovery of superconductivity with a maximum T c  ≈ 1.28 K in Br-doped (PbSe)1.12 (TaSe2 ), which is a new misfit compound consisting of alternating layers of distorted rocksalt PbSe and dichalcogenide TaSe2 . It is found that the Br-doping is required for the formation of this misfit compound and superconductivity can be tuned by the Br content. The large anisotropic parameter of resistivity γ ρ = ρ c / ρ ab  ≈ 100 and that of the upper critical field γ H c 2 = H c 2 ab / H c 2 c  ≈ 10 are obtained. The estimated c -axis coherence length ξ c  ≈ 6.3 nm, larger than the c -axis lattice constant, which implies that this compound is an anisotropic three-dimensional superconductor. The Hall coefficient measurements suggest that the charge transport is dominated by the hole-type charge carrier and there is a charge transfer from the PbSe layer to the conducting TaSe2 layer. The small normalized specific heat jump Δ C / γ T c  = 1.16 and electron–phonon coupling constant λ ep  ≈ 0.61 indicate that Br-doped (PbSe)1.12 (TaSe2 ) is a weak coupling Bardeen–Cooper–Schrieffer superconductor.